'I don't care about the city': the role of connections in job-related mobility decisions of skilled professionals. Issue 1 (1st January 2017) - Tippel, Cornelia; Plöger, Jörg; Becker, Anna
Abstract: Many cities in industrialized countries engage in competition for talent. While scholars have produced rich accounts of why some cities are better equipped than others in attracting skilled workers, the individual decision-making and agency of this group remains understudied. Contributing to this debate we examine how skilled professionals make their decisions in favour of locations. It focuses on the role of connections, which comprise social networks and take into account a range of professional, social and cultural ties between individuals and places. Our argument is based on empirical material from two qualitative case studies on work-related migration. The first studies professionals who moved to Frankfurt on a temporary basis from within Germany; the second focuses on high-skilled international migrants in Hamburg. We show that these supposedly privileged professionals often address limited job opportunities and personal constraints. Based on our findings and in addition to hard location factors, we argue that different forms of connections may further explain work-related moves. Despite similarities between the groups, internal migrants are more reliant on professional networks, while the international group is more likely to benefit from institutional connections. In our conclusion, we discuss how our research reveals inadequacies of current modes of urban policy-making.